The role of black-box models in rotorcraft attitude control - Bergamasco, M.; Cortigiani, N.; Del Gobbo, D.; Panza, S.; Lovera, M. (My University, 2017)
Black-box model identification methods of the subspace class can provide more accurate multivariable continuous-time state-space models with respect to frequency-domain procedures applied to structured models. The use of black-box models, however, comes with a number of issues, which have to be addressed to successfully employ them in the control design toolchain: the aim of this paper is to discuss the main issues which have to be dealt with before the raw black-box models can be effectively employed for control law design.